GAME AND CREATIVE TASKS AS A MEANS OF DEVELOPMENT COGNITIVE INTERESTS OF STUDENTS IN THE STUDY OF CHEMISTRY - N.O. Chuvasova (Academy of Cognitive and Natural Sciences, 2004)
The article is dedicated to the problem of the development of cognitive interests in chemistry lessons. The role o f creative and play tasks are shown as the means of the development of cognitive interests.